ANALISIS PENYEBAB TUNGGAKAN AIR PELANGGAN PADA PERUSAHAAN UMUM DAERAH AIR MINUM KOTA MAGELANG - Valent R, Untsa Aprimelia; Arifah, Siti (Journal Accounting International Mount Hope, 2025)
The analysis of the causes of customer water arrears aims to identify the factors that affect customers in making water bill payments This research uses descriptive qualitative methods, the research sources are primary and secondary data from interviews and library research. The results of this study know what are the factors that cause large customer water arrears receivables at Perumda Air Minum Kota Magelang, as well as knowing the consequences of customer water arrears and how the process of collecting water arrears. By knowing the factors that cause large customer arrears, the company can determine the right policy or strategy to reduce or avoid arrears.